Défaire le genre des représentations médiatiques et des dispositifs numériques - Nelly Quemener; Virginie Julliard (Communication)
By combining a cultural studies and semiotic approach to communication and media research, we have continuously tackled the difficult question of how to grasp power relationships and identify how they materialize in discourse. This article draws on our past research to reflect on the methodological issues involved in operationalizing a gender-based approach to the analysis of texts and images produced and disseminated on digital platforms and devices in the mainstream media.